2008
DOI: 10.1016/j.neuropharm.2008.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subtype-selective group I mGluR antagonists on synchronous activity induced by 4-aminopyridine/CGP 55845 in adult guinea pig hippocampal slices

Abstract: Co-application of the convulsant 4-aminopyridine (4-AP) and the GABA B receptor antagonist CGP 55845 to adult guinea pig hippocampal slices elicits giant GABA-mediated postsynaptic potentials (GPSPs) and epileptiform discharges. Here we tested the effects of the group I metabotropic glutamate receptor (mGluR) subtype-selective antagonists LY 367385 (mGlu1, 100 µM), MPEP (mGlu5, 10 µM), and MTEP (mGlu5, 500 nM) on this synchronous activity. Electrophysiological field recordings were performed in the CA3 region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The solution in the holding chamber where the slices were stored after cutting (Salah and Perkins 2008) contained (in mM) 125 NaCl, 25 NaHCO 3 , 2.5 KCl, 1.6 MgCl 2 , 2.0 CaCl 2 , 11 D-glucose. The 1.6 mM Mg 2+ /2.0 mM Ca 2+ extracellular recording solution contained (in mM) 130 NaCl, 24 NaHCO 3 , 2.5 NaH 2 PO 4 , 3.5 KCl, 1.6 MgSO 4 , 2.0 CaCl 2 , 10 D-glucose.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The solution in the holding chamber where the slices were stored after cutting (Salah and Perkins 2008) contained (in mM) 125 NaCl, 25 NaHCO 3 , 2.5 KCl, 1.6 MgCl 2 , 2.0 CaCl 2 , 11 D-glucose. The 1.6 mM Mg 2+ /2.0 mM Ca 2+ extracellular recording solution contained (in mM) 130 NaCl, 24 NaHCO 3 , 2.5 NaH 2 PO 4 , 3.5 KCl, 1.6 MgSO 4 , 2.0 CaCl 2 , 10 D-glucose.…”
Section: Methodsmentioning
confidence: 99%
“…The ionotropic glutamate receptor antagonists used were the AMPA/kainate receptor antagonist 2,3-dioxo6-nitro-1,2,3,4,-tetrahydrobenzo[f] quinoxaline-7-sulfonamide disodium salt (NBQX, 10 μM) and the NMDA receptor antagonist D-(−)-2-amino-5-phosphonopentanoic acid (D-AP5, 50 μM). The group I mGluR antagonists used were ( S )-(+)-α-amino-4-carboxy-2-methylbenzeneacetic acid (LY 367385, 100 μM; Salah and Perkins, 2008), which preferentially blocks the mGlu1 receptor subtype, and 2-methyl-6-(phenylethynyl)pyridine hydrochloride (MPEP, 10 μM; Salah and Perkins, 2008), which preferentially blocks the mGlu5 receptor subtype. The general protein synthesis inhibitor cycloheximide (60 μM) was used in some experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of glutamatergic-independent synchronous activity can be recorded from practically any limbic structures maintained in the brain slice (Avoli et al, 1996aBenini et al, 2003;Sudbury and Avoli, 2007;Panuccio et al, 2009) as well as in the isolated guinea pig brain (Uva et al, 2009). It has also been reported that the rate of occurrence of these GABAergic spikes are not influenced by modulating metabotropic glutamate receptor activity (Salah and Perkins, 2008).…”
Section: Involvement Of Gaba a Receptor-mediated Mechanisms In The Slowmentioning
confidence: 96%
“…This mechanism is unlikely in the Has3 KO mice, however, because the location of axon terminals of recurrent excitatory connections in CA1 is in the basal dendrites in SO (Deuchars and Thomson, 1996), not in the pyramidal cell layer where the reduced ECS volume fraction is localized (Arranz et al, 2014). Since the requirement is for ionotropic and not metabotropic glutamate receptors, presumably the glutamatergic transmission is needed for the trigger and/or synchronization mechanisms rather than to provide a sustained depolarization of the cell (see discussion in Salah and Perkins, 2008). …”
Section: Mechanism Of Generation Of Epileptic Events In the Has3 Ko Mmentioning
confidence: 99%